Method for inhibiting zinc dendrites of aqueous zinc battery
By constructing a modified tin layer on the surface of the zinc sheet, and induced the growth of deposited zinc along the (101) crystal surface using stannous chloride aqueous solution, the problem of difficulty in suppressing zinc dendrites in the prior art is solved, and better electrochemical performance is achieved.
Patent Information
- Application Number
- CN202411430865.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art is difficult to regulate the dense and uniform growth of deposited zinc along the (101) crystal surface by heterogeneous metal surface modification, thereby effectively inhibiting the growth of zinc dendrites.
By performing a replacement reaction on the surface of the zinc sheet, a modified tin layer was constructed using aqueous stannous chloride solution to induce dense and uniform growth of deposited zinc along the (101) crystal plane.
Effectively inhibit the growth of zinc dendrites, improve the electrochemical performance of zinc sheet negative electrode materials, and provide new ideas for the research on surface modification of zinc sheet negative electrode materials.
Smart Images

Figure CN119517924A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a method for inhibiting zinc dendrites in aqueous zinc batteries. Background Art
[0002] Aqueous secondary zinc batteries have the advantages of low cost and high safety, and are one of the important candidates for the next generation of green energy storage technology. The negative electrode material is usually zinc sheet, and the theoretical specific capacity of zinc metal negative electrode is 820mAh g -1 The redox potential is -0.76 V relative to the standard hydrogen electrode, and the application prospects are good. However, before practical application, the dendrite growth problem of zinc negative electrode needs to be reasonably solved.
[0003] Modification of the zinc / electrolyte interface is one of the most effective measures to inhibit dendrite growth. Figure 1 As shown in (A), the zinc hexagonal structure has (002) crystal plane, (100) crystal plane, (101) crystal plane, etc. Figure 1 As shown in (B), zinc is deposited unevenly on the commercial zinc sheet negative electrode material. Different crystal planes have different angles with the zinc sheet substrate, making the deposited zinc messy and uneven. At present, it is generally recognized in the field that the induction of deposited zinc growth with the (002) crystal plane is advocated, such as Figure 2 As shown in (C), the electrolyte is modified on the commercial zinc sheet to induce the deposited zinc to have a (002) crystal plane orientation, achieving a flat deposition morphology, thereby inhibiting the growth of dendrites. Therefore, a large number of literature studies are currently conducted to achieve the (002) crystal plane orientation of deposited zinc by surface modification of zinc sheet negative electrode materials. At present, there is no report on the technical solution of controlling the dense and uniform growth of deposited zinc along the (101) crystal plane by performing heterogeneous metal surface modification on zinc sheet negative electrode materials, thereby inhibiting the growth of zinc dendrites. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a method for inhibiting zinc dendrites in aqueous zinc batteries.
[0005] The technical solution adopted by the present invention is a method for inhibiting zinc dendrites in aqueous zinc batteries, which comprises the following steps:
[0006] (1) preparing stannous chloride aqueous solution;
[0007] (2) placing the zinc sheet in the solution prepared in step (1) to carry out a replacement reaction, thereby in-situ constructing a modified tin layer on the surface of the zinc sheet.
[0008] Preferably, the thickness of the modified tin layer is 60-80 nm.
[0009] Preferably, in step (1), the solution is prepared by mixing stannous chloride with ultrapure water at a mass concentration of 5 g / L.
[0010] The beneficial effects of the present invention are as follows: the present invention uses a stannous chloride aqueous solution to perform a replacement reaction on a zinc sheet, thereby in-situ constructing a modified tin layer on the surface of the zinc sheet. The modified tin layer constructed by this method can induce the deposited zinc to grow densely and uniformly along the (101) crystal plane, and it can effectively inhibit the growth of zinc dendrites, has better electrochemical properties, and provides a new idea for the study of surface modification of zinc sheet negative electrode materials. At the same time, the method provided by the present invention is simple and efficient, and has commercial application potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.
[0012] Figure 1 In the figure, (A) is a schematic diagram of the crystal plane of the hexagonal structure of zinc, (B) and (C) are cited from the accompanying drawings of the document AEM, 2023, 1(1), 2203254, which are respectively microscopic images of unevenly deposited zinc on a commercial zinc sheet negative electrode material and microscopic images of zinc deposited on a commercial zinc sheet by electrolyte modification and induction with a (002) crystal plane orientation;
[0013] Figure 2 X-ray diffraction data of tin-modified zinc negative electrode material;
[0014] Figure 3 This is a scanning electron microscope image of the tin-modified zinc negative electrode material;
[0015] Figure 4 Surface element distribution surface scan data of tin-modified zinc negative electrode material;
[0016] Figure 5 It is the cross-sectional element distribution surface scanning data of tin-modified zinc negative electrode material;
[0017] Figure 6 Atomic force microscopy image of the surface nano-region of the tin-modified zinc negative electrode material;
[0018] Figure 7 The simulation data of the surface current density distribution of tin-modified zinc negative electrode materials;
[0019] Figure 8 Simulation data of electrolyte concentration distribution on the surface of tin-modified zinc negative electrode material;
[0020] Fig. 9 Corrosion resistance test data of tin-modified zinc negative electrode materials;
[0021] Fig.10 The surface scan data of nano-scale cross-sectional element distribution of tin-modified zinc negative electrode materials;
[0022] Fig.11 In situ optical observation of zinc deposition characteristics on tin-modified zinc anode materials;
[0023] Fig.12 Deposition of 1 mAh cm on a Sn-modified Zn anode -2 SEM image of the surface capacity of zinc;
[0024] Fig.13 The scanning electron microscope cross-sectional view and schematic diagram of the tin-modified zinc negative electrode after deposition;
[0025] Fig.14 X-ray diffraction test analysis data for the induction effect of the tin modified layer on the crystal plane orientation of deposited zinc;
[0026] Fig.15 Cycling performance of tin-modified zinc anode materials;
[0027] Fig.16 The rate performance of tin-modified zinc anode materials;
[0028] Fig.17 X-ray diffraction data for commercial zinc sheet negative electrode materials;
[0029] Fig.18 This is a scanning electron microscope image of a commercial zinc sheet negative electrode material;
[0030] Fig.19 Atomic force microscopy image of the surface nano-region of a commercial zinc sheet negative electrode material;
[0031] Fig. 20 The simulation data of the surface current density distribution of commercial zinc sheet negative electrode materials;
[0032] Fig.21 Simulation data of electrolyte concentration distribution on the surface of commercial zinc sheet negative electrode materials;
[0033] Fig. 22 Corrosion resistance test data of commercial zinc sheet negative electrode materials;
[0034] Fig.23 In situ optical observation of zinc deposition characteristics on commercial zinc sheet anode materials;
[0035] Fig.24 Depositing 1 mAh cm on a commercial zinc sheet anode -2 SEM image of the surface capacity of zinc;
[0036] Fig.25The scanning electron microscope cross-sectional view and schematic diagram of the commercial zinc sheet negative electrode after deposition;
[0037] Fig.26 X-ray diffraction test data of the crystal plane orientation of zinc deposited on carbon paper;
[0038] Fig. 27 Cycling performance of commercial zinc sheet anode materials;
[0039] Fig.28 The rate performance of commercial zinc sheet anode materials. DETAILED DESCRIPTION
[0040] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.
[0041] Example 1: Experiment of soaking zinc sheet in stannous chloride aqueous solution
[0042] 0.5 g of stannous chloride was dissolved in 100 ml of ultrapure water and stirred for 5 minutes to obtain a solution. The zinc sheet was placed in the solution for 2 minutes, the zinc sheet was taken out, rinsed with ultrapure water, and dried naturally at room temperature to obtain a tin-modified zinc negative electrode material.
[0043] The X-ray diffraction data of the prepared tin-modified zinc anode material are as follows: Figure 2 As shown, the experimental results show that the modified layer is tin.
[0044] The scanning electron microscopy image of the prepared tin-modified zinc negative electrode material is shown in Figure 3 As shown, the experimental results show that the surface morphology of the material changes after the chemical replacement reaction.
[0045] The surface element distribution surface scanning data of the prepared tin-modified zinc negative electrode material are as follows Figure 4 As shown, the experimental results show that the Sn layer uniformly covers the zinc substrate.
[0046] The cross-sectional element distribution surface scan data of the prepared tin-modified zinc negative electrode material are as follows: Figure 5 As shown, the experimental results show that the Sn modified layer was successfully constructed.
[0047] The atomic force microscopy image of the surface nano-region of the prepared tin-modified zinc negative electrode material is shown in Figure 6 As shown, the experimental results show that the surface of the modified negative electrode is relatively flat at the nanoscale, without obvious "tips".
[0048] The simulation data of the surface current density distribution of the prepared tin-modified zinc negative electrode material is as follows: Figure 7 As shown, the experimental results show that the current density distribution on the surface of the modified negative electrode is uniform.
[0049] The simulation data of surface electrolyte concentration distribution of the prepared tin-modified zinc negative electrode material is as follows: Figure 8 As shown, the experimental results show that the electrolyte concentration distribution on the surface of the modified negative electrode is uniform.
[0050] The corrosion resistance test data of the prepared tin-modified zinc negative electrode material are as follows: Fig. 9 The experimental steps are as follows: first, the modified negative electrode is immersed in zinc sulfate electrolyte for 9 days, then taken out, rinsed and dried at room temperature, and then its surface is characterized by scanning electron microscopy to observe surface changes. The experimental results show that the surface changes of the modified negative electrode are relatively uniform, and there is no obvious stacking and aggregation of corrosion products.
[0051] The focused ion beam technique was used to prepare samples suitable for transmission electron microscopy characterization, and the tin layer thickness of the tin-modified zinc negative electrode material was analyzed. The cross-sectional element distribution surface scanning data at the nanoscale level were Fig.10 As shown, it can be seen that the thickness of the tin layer formed on the surface of the zinc sheet is about 70nm.
[0052] Example 2: In-situ optical observation of zinc deposition behavior
[0053] The tin-modified zinc negative electrode material prepared in Example 1 was observed in real time by using an Olympus optical microscope and a self-designed optical cell. The zinc deposition characteristics on the modified zinc sheet were observed. The test parameters were a current density of 5 mA cm -2 , test data such as Fig.11 As shown, the deposited morphology is dense and uniform, without dendrite growth.
[0054] Example 3: Scanning electron microscope observation of the morphology of deposited zinc
[0055] The surface morphology of the deposited zinc was observed using a scanning electron microscope. A 2032-type button-type symmetrical battery was assembled, and the components included a negative electrode shell, the tin-modified zinc negative electrode material prepared in Example 1, a diaphragm, the tin-modified zinc negative electrode material prepared in Example 1, a gasket, and a positive electrode shell. The electrolyte was 100 μl of a 2M Zn2SO4 aqueous solution. At 5 mA cm -2 Current density, deposited 1 mAh cm -2 The SEM image of the electrode with the surface capacity is shown in Fig.12 As shown in Figure 3, the deposited morphology is dense and uniform, indicating that the Sn modified layer effectively inhibits the growth of Zn dendrites.
[0056] The cross-sectional morphology of deposited zinc was observed using a scanning electron microscope. Fig.13As shown, it was found that the tin-modified negative electrode presented a uniform and flat deposition morphology, and the tin layer regulated the deposition of zinc along the Zn (101) crystal plane. The specific analysis is as follows: the crystal orientation of the zinc grains is 65° to the modified electrode surface. It is known that zinc is parallel to the substrate when deposited along the (002) crystal plane, and the crystal plane angle between the (101) and (002) planes of the hexagonal zinc crystals is 65°. Based on this crystallographic characteristic, it can be cleverly analyzed that the zinc deposited on the tin-modified zinc negative electrode grows along the Zn (101) crystal plane.
[0057] Example 4 Analysis of the Inducing Effect of the Tin Layer on the Crystalline Orientation of Deposited Zinc
[0058] First, 3 mAh cm was deposited on carbon paper. -2 The surface capacity of zinc was used to obtain the (carbon paper-zinc) material. The deposition method was to assemble the carbon paper into a symmetrical button cell and -2 The current density was deposited using a 2M Zn2SO4 electrolyte. Then, according to the method of Example 1, the (carbon paper-zinc) material was immersed in a stannous chloride aqueous solution for a replacement reaction. The above solution was prepared by dissolving 0.5 g of stannous chloride in 100 ml of ultrapure water. After reacting for 5 minutes, the material was taken out and rinsed several times with ultrapure water to obtain a (carbon paper-tin) material, which was subjected to an X-ray diffraction test. Finally, 5 mA cm -2 The current density was deposited for 15 minutes, using 2M Zn2SO4 electrolyte, and the material was taken out for X-ray diffraction test. The test data is as follows Fig.14 As shown, the results indicate that the modified Sn layer can induce the deposited Zn to grow along the (101) crystal plane.
[0059] Example 5: Electrochemical performance test
[0060] Assemble 2032 type button-type symmetrical cells, the components include the negative electrode shell, the tin-modified zinc negative electrode material prepared in Example 1, the separator, the tin-modified zinc negative electrode material prepared in Example 1, the gasket and the positive electrode shell. The electrolyte is 100 μl of a 2M Zn2SO4 aqueous solution. The cycling performance is tested using a Xinwei battery tester at a constant current surface density. The test parameters are a current density of 5 mA cm -2 , with a surface capacity of 1 mAh cm -2 The test data is as follows: Fig.15 As shown in the figure, it can be seen that the modified zinc negative electrode material has a current density of 5 mA cm -2 , with a surface capacity of 1 mAh cm -2 Under the same conditions, the battery can be stably charged and discharged for 685 hours. The rate performance was tested using a Xinwei battery tester with current densities of 1 / 2 / 3 / 5 / 8 mA cm -2 , with a surface capacity of 1 mAh cm -2Each current density test is 10 cycles of charge and discharge, the test data is as follows Fig.16 As shown, the experimental results show that the tin-modified zinc negative electrode material has good rate performance, and the Sn layer regulates the electrode reaction kinetics.
[0061] Comparative Example 1:
[0062] The commercial zinc flakes were characterized by X-ray diffraction, scanning electron microscopy, atomic force microscopy and finite element simulation.
[0063] X-ray diffraction data of commercial zinc sheet negative electrode materials are as follows Fig.17 As shown, the experimental results indicate that the zinc flakes are polycrystalline.
[0064] The scanning electron microscope image of the commercial zinc sheet negative electrode material is as follows Fig.18 As shown, the experimental results show that there are micro defects on the surface of the zinc sheet.
[0065] Atomic force microscopy images of the surface nanoscale regions of commercial zinc sheet negative electrode materials Fig.19 As shown, the experimental results indicate that the zinc sheet surface has obvious "tips" at the nanoscale, which affects the electric field and concentration field distribution on the electrode surface.
[0066] The simulation data of the surface current density distribution of commercial zinc sheet negative electrode materials is as follows: Fig. 20 As shown, the experimental results show that the current density distribution on the surface of the zinc sheet is uneven.
[0067] The simulation data of the surface electrolyte concentration distribution of commercial zinc sheet negative electrode materials are as follows: Fig.21 As shown, the experimental results show that the electrolyte concentration distribution on the surface of the zinc sheet is uneven.
[0068] The corrosion resistance test data of commercial zinc sheet negative electrode materials are as follows: Fig. 22 The experimental steps are as follows: first, the zinc sheet is immersed in zinc sulfate electrolyte for 9 days, then taken out, rinsed and dried at room temperature, and then its surface is characterized by scanning electron microscopy to observe surface changes. The experimental results show that there is obvious stacking and aggregation of corrosion products on the surface of the zinc sheet, and the zinc sheet has poor resistance to electrolyte corrosion.
[0069] Comparative Example 2:
[0070] Real-time cross-sectional observation of zinc deposition characteristics of commercial zinc sheet anode material using an Olympus optical microscope and a self-designed optical cell. The test parameters are a current density of 5 mA cm -2 , test data such as Fig.23 As shown, the dendrite growth phenomenon is clearly seen.
[0071] Comparative Example 3:
[0072] The surface morphology of zinc deposited on the commercial zinc sheet was observed by scanning electron microscopy. A 2032-type button-type symmetrical battery was assembled, and the components included a negative electrode shell, a commercial zinc sheet negative electrode material, a separator, a commercial zinc sheet negative electrode material, a gasket, and a positive electrode shell. The electrolyte was 100 μl of a 2M Zn2SO4 aqueous solution. -2 Current density, deposited 1 mAh cm -2 The SEM image of the electrode with the surface capacity is shown in Fig.24 As shown, the unevenly deposited Zn is randomly interwoven with the separator, indicating that the Zn dendrite growth has pierced the separator.
[0073] The cross-sectional morphology of deposited zinc was observed using a scanning electron microscope. Fig.25 As shown in Figure 2, obvious zinc dendrite growth occurs on the commercial zinc sheet.
[0074] Comparative Example 4:
[0075] First, the carbon paper was charged at 5 mA cm -2 The current density was deposited for 15 minutes using 2M Zn2SO4 electrolyte, then taken out for cleaning, drying and X-ray diffraction test. The data are shown in Fig.26 As shown, the deposited zinc has no obvious preferred orientation.
[0076] Comparative Example 5:
[0077] Assemble 2032 button-type symmetrical cells, including negative electrode shell, commercial zinc sheet negative electrode material, separator, commercial zinc sheet negative electrode material, gasket and positive electrode shell. The electrolyte is 100 μl of 2M Zn2SO4 aqueous solution. The cycling performance is tested using a Xinwei battery tester at a constant current surface density. The test parameters are a current density of 5 mA cm -2 , with a surface capacity of 1 mAh cm -2 The test data is as follows: Fig. 27 As shown in the figure, it can be seen that the commercial zinc sheet negative electrode material has a current density of 5 mA cm -2 , with a surface capacity of 1 mAh cm -2 Under the same conditions, the stable charge and discharge cycle is less than 50 hours. The rate performance is tested using a Xinwei battery tester with current densities of 1 / 2 / 3 / 5 / 8 mA cm -2 , with a surface capacity of 1 mAh cm -2 Each current density test is 10 cycles of charge and discharge, the test data is as follows Fig.28 As shown, the experimental results show that the rate performance of commercial zinc sheet negative electrode materials is poor.
[0078] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.
Claims
1. A method for inhibiting zinc dendrites in aqueous zinc batteries, characterized in that It includes the following steps: (1) preparing stannous chloride aqueous solution; (2) placing the zinc sheet in the solution prepared in step (1) to carry out a replacement reaction, thereby in-situ constructing a modified tin layer on the surface of the zinc sheet.
2. The method for inhibiting zinc dendrites in aqueous zinc batteries according to claim 1, characterized in that: The thickness of the modified tin layer is 60-80 nm.
3. The method for inhibiting zinc dendrites in aqueous zinc batteries according to claim 2, characterized in that: In step (1), the solution is prepared by mixing stannous chloride and ultrapure water at a mass concentration of 5 g / L.